Improving the Community's Economy Through Creative Waste Products in Sanja Village - Fahrudin, Alifiya Septiyan; Rinda, Rachmatullaily Tinakartika (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
The purpose of this community service is to improve the community's economy through creative waste products in Sanj Village and the method used is qualitative descriptive. the result of this activity is that residents are very enthusiastic, and very actively partitioned to participate in the activity so that the process of making plastic waste recycling creations of residents follows the activation process to the end without leaving the place of activity where the process of recycling plastic waste consists of the collection, Sorting, and processing where there is awareness, enthusiasm, and willingness supported by the need for raw materials that are cheap and easy to find.